2010
DOI: 10.1177/0003319710366431
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rosiglitazone on Fasting and Postprandial Low- and High-Density Lipoproteins Size and Subclasses in Type 2 Diabetes

Abstract: Rosiglitazone may increase cardiovascular risk in patients with type 2 diabetes. Yet, its effects on atherogenic dyslipidemia are still not fully elucidated. In a prospective open-label study rosiglitazone (4 mg/day for 12 weeks) was added to a maximum of 2 oral antidiabetic drugs in 18 diabetic patients. We evaluated the effects on plasma lipids before and after an oral fat load. The size and subclasses of low-density lipoprotein (LDL) and high-density lipoprotein (HDL) were also determined (by gradient gel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…In another study, it was demonstrated that both HDL2 and HDL3 protect against CVD [41]. However, most studies that investigate the therapeutic modulation of HDL subfraction demonstrate that larger HDL particles are more protective against CVD [42]. In sum, according to a review article by Rizzo et al, further clinical investigations are required to clarify the physicochemical and functional heterogeneity of HDL subfractions [38].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was demonstrated that both HDL2 and HDL3 protect against CVD [41]. However, most studies that investigate the therapeutic modulation of HDL subfraction demonstrate that larger HDL particles are more protective against CVD [42]. In sum, according to a review article by Rizzo et al, further clinical investigations are required to clarify the physicochemical and functional heterogeneity of HDL subfractions [38].…”
Section: Discussionmentioning
confidence: 99%
“…It is important that changes in LDL2 and LDL4 were also independent of the use of specific classes of glucose-lowering medications, including insulin or rosiglitazone, that previously were shown to increase LDL particle size (1821,24,28). In contrast with some previous studies (18,19,24), changes in LDL subclasses in our cohort were not related to insulin use.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a comprehensive review article by Rizos et al has previously shown that thiazolidinediones favorably alter fat distribution and improve cardiovascular risk factors, such as blood pressure, inflammation markers and uric acid, and may also delay the progression of atherosclerosis [7]. However, the effects on the lipid profile significantly differ between the two agents in this class, with pioglitazone overall having more positive effects compared with rosiglitazone; indeed, pioglitazone has been shown to be able to significantly reduce the atherogenicity of lipoproteins, including small, dense low-density lipoproteins (LDL) [8][9][10].…”
Section: Non-glycemic Effects Of Pioglitazonementioning
confidence: 99%